Active Controller Design for Microgravity Isolation Systems - Nan-Chyuan Tsai (Shock and Vibration)
This paper examines the performance of active isolation systems for microgravity space experiments as a function of desired transmissibilities that are chosen to be either much below or close to what can be tolerated. The control system utilizes two feedback signals: absolute acceleration and relative displacement of the controlled mass. The controller transfer function for acceleration feedback is chosen to avoid marginally stable pole-zero cancellations. The controller transfer function for relative displacement feedback is determined to achieve the desired transmissibility function. The issue of stability and properness of this controller transfer function are discussed. The required input forces and equivalent closed-loop stiffness are examined for various examples of desired transmissibilities.